Peran Sistem Informasi Manajemen Kepegawaian (SIMPEG) dalam Transformasi Digital Birokrasi di Kantor Wilayah Kementerian Hukum Sumatera Barat - Marshanda, Serli; Fitri, Fitri; Hadira, Sabhena Binta; Zalino, Audri Putri; Hanoselina, Yulia (Inovan Publisher, 2025)
The employee management information system (simpeg) is a digital system that facilitates digital-based personnel administration processes, making it easier to manage integrated employee data. one of the institutions promoting this innovation is the regional office of the ministry of law in west sumatra in managing personnel data. At the regional officeof the ministry of law in west sumatra, the employee management information system (simpeg) has been implemented since 2015. This study aims to examine the role of the employee management information system (simpeg) in the digital transformation of bureaucracy at the regional office of the ministry of law in west sumatra. This research uses aqualitative method with data collection techniques through interviews and documentation to identify the roles, benefits, and challenges in the implementation of the employee management information system (simpeg). Research results indicate that the personnel management information system (simpeg) provides convenience in managing employee data such as attendance, performance evaluation, promotions, and others. However, there are still challenges in the personnel management information system (simpeg), such as synchronization processes that need further development.